Peningkatan Pengetahuan dan Pelatihan Selling Skill: “Consumers Evaluation of Services” Karyawan di PT Kimia Farma Apotek Unit Bisnis Surabaya - Parwati, Dian (Akademi Farmasi YPPM Mandiri, 2023)
A pharmacy is a pharmaceutical service facility where pharmacists practice pharmacy. Pharmacy practice is assisted by Pharmacy Technical Staff, consisting of Pharmacy Bachelors, Pharmacy Associate Experts, and Pharmacy Analysts. The orientation of pharmaceutical services is starting to shift from orientation to product service or product oriented to services that aim to improve patient’s quality of life or patient-oriented. One of the roles of pharmaceutical services is reviewing prescriptions, dispensing, counseling, Drug Information Services (PIO), and others to obtain the best recommendations for patients. However, a pharmacy is not only a place for pharmaceutical services but is also grouped as a line of business according to the Indonesian Business Field Standard Classification (KBLI) with code 47721, namely the retail trade of pharmaceutical goods and drugs for humans in pharmacies. One of the goals of selling these goods is to get a profit. Even though seeking profit/profit is not the professional duty of a pharmacist, it is an indicator that the pharmacy is still growing. One of the efforts made is Increasing Knowledge and Selling Skill Training for Associate Pharmacists and Pharmacy Technical Personnel at PT Kimia Farma Pharmacy Surabaya Business Unit. The existence of this activity is expected to be able to educate and have an impact on increasing profits in accordance with pharmaceutical service standards and scientific principles. The results obtained in the implementation are: (1) Increased interest and awareness of participants to play a role in carrying out pharmaceutical services according to standards (2) Increased knowledge of participants about selling skills seen from the patient's perspective (3) Participants know how to increase positive perspectives after patients come to the pharmacy.